Discovery of honokiol thioethers containing 1, 3, 4-oxadiazole moieties as potential α-glucosidase and SARS-CoV-2 entry inhibitors. (1st August 2022) - Xu, Ting; Meng, Jie-Ru; Cheng, Wanqing; Liu, Jia-Zheng; Chu, Junyan; Zhang, Qian; Ma, Nannan; Bai, Li-Ping; Guo, Yong
Graphical abstract: Highlights: Two series of honokiol thioethers bearing 1, 3, 4-oxadiazole moieties were prepared. Compound 7l exhibited the strongest α -glucosidase inhibitory activity. Both enzyme kinetic and molecular docking studies indicated that 7l was a noncompetitive α -glucosidase inhibitor. Compound 9a displayed potent inhibitory effect against SARS-CoV-2 pseudovirus. Abstract: Honokiol, isolated from a traditional Chinese medicine (TCM) Magnolia officinalis, is a biphenolic compound with several biological activities. To improve and broaden its biological activity, herein, two series of honokiol thioethers bearing 1, 3, 4-oxadiazole moieties were prepared and assessed for their α -glucosidase and SARS-CoV-2 entry inhibitory activities. Among all the honokiol thioethers, compound 7l exhibited the strongest α -glucosidase inhibitory effect with an IC50 value of 18.9 ± 2.3 µM, which was superior to the reference drug acarbose (IC50  = 24.4 ± 0.3 µM). Some interesting results of structure–activity relationships (SARs) have also been discussed. Enzyme kinetic study demonstrated that 7l was a noncompetitive α -glucosidase inhibitor, which was further supported by the results of molecular docking. Moreover, honokiol thioethers 7e, 9a, 9e, and 9r exhibited potent antiviral activity against SARS-CoV-2 pseudovirus entering into HEK-293 T-ACE2 h . Especially 9a displayed the strongest inhibitory activity against SARS-CoV-2 pseudovirus entry with an IC50 value of 16.96 ± 2.45 μM, which was lower than the positive control Evans blue (21.98 ± 1.98 μM). Biolayer interferometry (BLI) binding and docking studies suggested that 9a and 9r may effectively block the binding of SARS-CoV-2 to the host ACE2 receptor through dual recognition of SARS-CoV-2 spike RBD and human ACE2. Additionally, the potent honokiol thioethers 7l, 9a, and 9r displayed relatively no cytotoxicity to normal cells (LO2). These findings will provide a theoretical basis for the discovery of honokiol derivatives as potential both α -glucosidase and SARS-CoV-2 entry inhibitors.